Swimming stroke parameters and their effects on performance - Ertas Dolek, B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Stroke parameters and their effects on performance and efficiency is a subject of swimming studies for a long time. The purpose of this study was to investigate the relationship between stroke rate (SR), stroke count (SC) and performance due to the changes in heart rate (HR) and lactic acid (LA) levels of swimmers during a 4x(4x100m) front crawl (freestyle) main set of three consecutive training days. In this study, 7 male (age = 14.14 ± 1.07) and 4 female (age = 14.00 ± 0.00) international level swimmers were participated. Before the study, swimmers` detailed body analyzes have been taken. For male and female swimmers, height (H = 175.28 ± 4.02; 163.25 ± 5.56), weight (W = 69.94 ± 4.20; 58.97 ± 2.77), body mass index (BMI = 22.77 ± 1.56; 22.15 ± 0.86) and percentage of body fat (PBF = 14.3 ± 7.17; 25.05 ± 2.18) data are obtained (Mean ± Standard Deviation, respectively). During the study, SC (for every 100m), SR (for each 75th.m), HR (for the end of every 100m), 100m-lap-times (for each 100m LAP), LA measurements (for the end of every 4x100m) were measured. Relationship between SR, SC, HR, LAP and LA was calculated using Statistical Package for Social Sciences (SPSS) v. 22.0. A cut of point in all the statistical analyses has been taken as p 0.05.